The Elusive Presence of God in Ezekiel’s Exagoge: A Proposal for Reading a Fragmented Text - Calderbank, Annie (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2026)
This article investigates the Exagoge of Ezekiel the tragedian as a sophisticated reflection on the possibilities and the challenges of inferring divine presence. It thus situates the ambiguities of Moses’s remarkable throne vision, which have been fuel for scholarly debate, within a wider account of divine presence across the play. The article also proposes an approach to reading the Exagoge’s fragmented text that focuses on the linguistic and literary interconnections within and between the fragments. It explores the Exagoge’s engagement with biblical traditions, not as alignment with or divergence from sources, but as contributing to the dialogue between scenes, enabling inference, irony, and anticipation. It also attends to the role of the Exagoge’s editors, Polyhistor and Eusebius, in shaping the portrayal of divine presence in the preserved fragments, including in ways that reinforce connections between the fragments and their narrative arc.